Epigenetic Mechanisms of Cardioprotection: Focus is on Activation of Sirtuins - K. A. Aitbaev; I. T. Murkamilov; Zh. A. Murkamilova; I. O. Kudaibergenova; F. A. Yusupov (Архивъ внутренней медицины, 2021)
Oxidative stress is a common sign of aging and cardiovascular disease (CVD), including atherosclerosis, heart failure, hypertension, diabetes mellitus and other diseases of the vascular system. In this regard, in recent years, researchers have shown increased interest in sirtuins (SIRTs) — stress adapters and epigenetic enzymes involved in cellular mechanisms for controlling age-related pathologies, cancer and CVD. Among sirtuins, of which there are seven in mammals (SIRT1-SIRT7), SIRT1 and SIRT6 possess the most cardioprotective, anti-inflammatory, atheroprotective and anti-aging properties. In this review, we present a comprehensive analysis of the latest developments in the field of cellular and molecular signaling pathways controlled by two post-translational modifiers — SIRT1 and SIRT6, which have proven their worth as tools to reduce inflammation and oxidative stress at the level of the cardiovascular system. A deeper understanding of the epigenetic mechanisms through which SIRT1 and SIRT6 exert their cardioprotective effect will have widespread implications and will accelerate the development of selective and effective pharmacological agents for modulating sirtuins for the prevention and treatment of CVD.